Urban Ruins and the Neo -Picturesque Landscape - Scarbrough, Elizabeth (Aesthetic Investigations, 2023)
While classical ruins are seen as tourist destinations, contemporary or industrial ruins are dismissed as disused sites. In this paper I argue for the preservation of urban (or contemporary) ruins. I focus on one specific case, that of the Miami Marine Stadium in Miami, Florida USA. Since the 1990s the stadium has been derelict, a canvas for graffiti artists and a home to skateboarders. In 2018 the City of Miami decided to revamp the stadium and reopen it as a concert and sporting venue. The current design-development plan has sanitized this urban ruin, robbing it of its past. I will situate the debate about rehabbing contemporary ruins within the growing literature of the neo-picturesque, specifically neo-picturesque landscape design. I believe that urban ruins such as these have a place in the modern city and will suggest some paths forward for these neo-picturesque ruin beauties.